The experience of bodily image for patients with left ventricular assist device - Milaniak, Irena; Witkowska, Emilia; Cebula, Marta; Tomsia, Paulina; Wasilewski, Grzegorz; Górkiewicz-Kot, Izabela; Wiśniowska-Śmiałek, Sylwia; Kaleta, Michał; Wierzbicki, Karol (Frontiers in Psychiatry, 2025)
IntroductionMechanical Cardiac Support and Left Ventricular Assist Devices (LVAD) have been demonstrated to prolong Heart Failure patients' survival and improve their quality of life. LVAD implantation has a considerable effect on patients' body image. Patients find it hard to accept the device as an extension of their body, especially the driveline. The study aimed to examine the relationships between anxiety and depressive symptoms, acceptance of illness, beliefs about pain control, and quality of life with body image among LVAD-implanted patients.MethodsThe cross-sectional study included 54 conveniently recruited patients who completed the Body Image Scale, SF-12, Acceptance of Illness Scale, Beliefs about Pain Control Questionnaire, NRS, HADS, and demographic and clinical data. Multiple regression analyses examined the associations between the research variable.ResultsThe mean Age of the participants was 59.64 (SD=9.63), and 96.3% were men. The mean scores were: Body Image Scale – 28.33 (SD=5,91); Acceptance of Illness Scale – 25.51 (SD=5.92); beliefs about pain control: internal factors – 15.85 (SD=4.96), the influence of physicians – 17.57 (SD=3.15), random events – 14.37(SD=3.32), NRS=2.80(SD=1.86), HADS anxiety – 5.33 (SD=4.12), HADS depression – 4.66 (SD=3.10), SF12MCS-45.49 (SD=6.48), SF-12PCS-41,33 (SD=6.48). The presence of anxiety and depressive symptoms and complications after LVAD significantly predicted low body image concerns.DiscussionHealthcare professionals should be aware of challenges regarding body image faced by LVAD-implanted patients and address related factors, especially anxiety and depression.